Transforming Education Policy: From National Assessment to National Exam and Its Impact on Learning Quality in Indonesia - Chaniago, Syahril; Hazar, Imam Ibnu; Mahwaty, Lia (JPG (Jurnal Pendidikan Geografi), 2025)
Education policy in Indonesia has undergone a significant shift from the National Assessment (AN) back to the National Examination (UN). This transition reflects concerns about infrastructure readiness, assessment effectiveness, and policy continuity. Using a qualitative approach, this study compares AN and UN, evaluating their implications for learning quality, equity, and systemic readiness. The findings highlight that while AN promotes holistic education by assessing literacy, numeracy, and character development, its implementation is hindered by technological and resource disparities. Conversely, the UN provides clear benchmarks and familiarity but risks prioritizing rote memorization over critical thinking. The study underscores the need for a balanced education evaluation framework that integrates the strengths of both assessments. A hybrid model combining standardized evaluation with competency-based assessments could enhance educational outcomes. Policymakers must consider sustainable education reforms that align with Indonesia’s development goals while ensuring equitable access to quality education.